2005
DOI: 10.1124/dmd.105.006270
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization and Haplotype Analysis of Polymorphisms in the Human Equilibrative Nucleoside Transporter, Ent2

Abstract: ABSTRACT:The equilibrative nucleoside transporter 2 (ENT2; SLC29A2) is a bidirectional transporter that is involved in the disposition of naturally occurring nucleosides as well as a variety of anticancer and antiviral nucleoside analogs. The goal of the current study was to evaluate the function of genetic variants in ENT2 in cellular assays and to determine the haplotype structure of the coding and flanking intronic region of the gene. As part of a large study focused on genetic variation in membrane transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…The substrate specificity of ENBT1/SLC43A3 is similar to that of Na + -independent purine nucleobase transport systems that are different from those of ENT1 and ENT2, which include carrier-mediated transport systems characterized in many types of cells, including human erythrocytes, 52) COR-L239, 40) LLC-PK1, 17) PK15NTD, 53) rat cortical neurons, 54) human and mouse primary microvascular endothelial cells, 34,45) and rabbit cornea epithelial cells. 55) ENBT1/ SLC43A3 selectively mediates the transport of purine nucleobases such as guanine, hypoxanthine, xanthine, and adenine, but not that of nucleosides.…”
Section: Enbt1/slc43a3mentioning
confidence: 98%
See 1 more Smart Citation
“…The substrate specificity of ENBT1/SLC43A3 is similar to that of Na + -independent purine nucleobase transport systems that are different from those of ENT1 and ENT2, which include carrier-mediated transport systems characterized in many types of cells, including human erythrocytes, 52) COR-L239, 40) LLC-PK1, 17) PK15NTD, 53) rat cortical neurons, 54) human and mouse primary microvascular endothelial cells, 34,45) and rabbit cornea epithelial cells. 55) ENBT1/ SLC43A3 selectively mediates the transport of purine nucleobases such as guanine, hypoxanthine, xanthine, and adenine, but not that of nucleosides.…”
Section: Enbt1/slc43a3mentioning
confidence: 98%
“…This raises the possibility that ENT2 expressed in the lung plays a role in the regulation of extracellular adenosine levels, rather than salvaging the intracellular purine. Genomic analysis revealed that single-nucleotide polymorphism (SNP) frequency in ENT2 is extremely low, 45) suggesting that it plays a crucial role in nucleotide synthesis and metabolism. Further studies are needed to elucidate the role of ENT2 as a nucleobase transporter.…”
Section: Facilitative Transport Systemsmentioning
confidence: 99%
“…This approach has been applied to many pharmacogenetic investigations of membrane transporters, which are important mediators of drug absorption and elimination and are also targets of many drugs. Significant effort has been invested in resequencing transporter genes in LCLs from the Studies of Pharmacogenetics in Ethnically Diverse Populations participants, followed by functional characterization using in vitro assays in Xenopus laevis oocytes or human cell lines such as human embryonic kidney 293 cells (Osato et al, 2003;Gray et al, 2004;Badagnani et al, 2005Badagnani et al, , 2006Fujita et al, 2005;Owen et al, 2005Owen et al, , 2006Urban et al, 2006bUrban et al, , 2007Abla et al, 2008;Huang et al, 2008a;Sorani et al, 2008;Chen et al, 2009;Miller et al, 2009;Yee et al, 2009). More recently, these LCLs, along with HapMap LCLs, have been used in functional studies as well, particularly involving allelic expression imbalance.…”
Section: Application Of Lymphoblastoid Cell Line Models In Pharmacogementioning
confidence: 99%
“…These results suggest that coding region variants of hENT1 do not contribute to inter-individual differences in response to nucleoside drugs. Fourteen polymorphic sites, including 11 in the coding region, were found in hENT2 at very low frequencies [112]. Five of the altered hENT2 variants (three nonsynonymous variants and two deletions) were able to transport inosine; one variant, which resulted in a premature truncation of hENT2, was not.…”
Section: Genetic Variants Of Hents and Hcntsmentioning
confidence: 99%